European Actorness in a Shifting Geopolitical Order European Strategic Autonomy Through Differentiated Integration - Rieker, Pernille; Giske, Mathilde T. E. (The European Union in International Affairs, 2024)
"The successive crises the EU has undergone, notably with the pandemic and Russia's invasion of Ukraine, have highlighted dramatically how European security includes while spans well beyond defence. Picking up from this cue, this book masterfully expands the notion of European strategic autonomy across different areas while highlighting its fundamental compatibility with the goal of building stronger partnerships beyond the EU's borders." - Nathalie Tocci, director at IAI in Rome "European Actorness in a Shifting Geopolitical Context is a timely and thought-provoking contribution to the discourse on European strategic autonomy. Rieker and Giske go beyond conventional notions of defence to highlight the pressing need to address the growing risk of hybrid threats. With meticulous research and a nuanced understanding of contemporary debates on European integration and security, this volume presents a comprehensive approach to fleshing out European strategic autonomy. Amust-read for policymakers, academic experts and anyone interested in understanding Europe's evolving role on the international stage." - Mark Leonard, director of ECFR "Rieker and Giske provide an innovative analysis of how external differentiation can help improve EU actorness and security. This is the first study that systematically brings together two core issues in European integration: external differentiation and strategic autonomy. Building on a broad empirical basis, the book makes an important contribution to current political and academic discussions on Europe's foreign and security policy." - Frank Schimmelfennig, Professor, ETH Zurich This is an open access book. Over the past decade, the global geopolitical context has changed significantly, with a geopolitical power shift and a more assertive Russia and China. With the unprovoked Russian invasion of Ukraine, European security has been put on high alert. The implications of the Russian military invasion are many and difficult to grasp in full. But the need for greater European strategic autonomy appears increasingly evident. But how can this be achieved in the short run? A common answer to this question is that it is impossible or that this can only be achieved in the long run, if at all. The aim of this book is to present a different perspective. It aims at showing that it should be possible to make the most out of the current European system if we adjust our understanding of how it works. The book argues that strategic autonomy may be reached-also in the short run-if differentiated integration (DI) is seen as an asset rather than a challenge. While the EU remains the core in such a system (together with NATO in the military domain), there is a multitude of other (bilateral and minilateral) regional and sub-regional integration processes that need to be considered to get the full idea of how a more differentiated European strategic autonomy can be achieved. This book starts by presenting a theoretical framework for how to study European actorness beyond the EU (ch.2), then this framework is applied both to understand Europe as a global actor (ch. 3), Europe as an actor in security and defence (ch. 4) and Europe as a regional actor (ch. 5). Pernille Rieker holds a position as a research professor at the Norwegian Institute of International Affairs (NUPI) and a part-time full professor at the Inland University College (INN). Rieker is part of NUPI's research group on security and defence and is responsible for NUPI's Center for European Studies (NCE). Furthermore, she is the co-editor of the Scandinavian journal for international studies, 'Internasjonal Politikk'. Mathilde E. Giske is a Ph.D. candidate, Department for Political studies, University of Oslo, Oslo, Norway.